Pedagogical benefits of a new student exercise - Snitkjær, Pia (Improving University Science Teaching and Learning, 2023)
‘Food Science and Culinary Techniques’ is an MSc course offered at KU-FOOD that has faced important challenges due to both the very broad educational background of the students and practical hurdles. The course is continuously being improved and there is a great potential to strengthen various pedagogical aspects of the course. A new practical exercise within the topic ‘baking’ has been developed for the 2016 version of the course. From a pedagogical point of view, the new exercise will potentially improve the amount and quality of formative assessment in the course, it will contribute to student engagement and self-directed learning, it will support learning of both disciplinary and general scientific competences and it will strengthen the student’s communication skills.